Penggunaan Bahasa Persuasi dan Elemen Bahasa pada Iklan Makanan di YouTube - Rahma Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to identify the use of persuasive language and language elements in food advertisements on the YouTube platform. Food advertising on digital media is an effective means of attracting consumer attention. With a qualitative descriptive approach, this research reveals various persuasion language techniques, such as the use of invitations and suggestions such as